Analysis of the wine production sector in the Czech Republic and Germany - Renata Černíková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2004)
The paper analyzes the current situation and the development in the wine production sector in the Germany and compares it with the situation in the wine production sector in the Czech Republic. The aim is to find identical trends and differences in the production and consumption of wine and foreign trade with wine in the both countries. The aim also is to define the main opportunities and threats for German wine producers in the Czech market and for Czech wineries in the German market.The domestic production is not able to cover the domestic consumption of wine in the both analyzed countries that is why wine is necessary to import. The domestic production covered only 52% of the domestic consumption in the Germany and only 41% of the domestic consumption in the Czech Republic in the analyzed years on average. The proportion in the production of red and white wine is identical in the Germany and in the Czech Republic as well (in the Germany in 2002 white wine 65%, red wine 35%; in the CR white wine 72%, red wine 28%). There is also the unbalanced foreign trade with wine in the both countries.The main difference of the Germany and the Czech wine market is possible to find in the size of the both markets. The German wine market is twelve times bigger according to the total consumption volume; the average annual consumption of wine varied about 24 litres per inhabitant. In the Czech Republic the wine consumption was increasing in the last 10 years, though the average year consumption of wine was only 14 litres per inhabitant in 2002.In contrast to the Czech Republic the Germany has very high stocks of wine (in 2001/2002 the wine stock was 14765 thousand hectolitres; 74% of domestic consumption), and very high share (94% in 2002) of the merging wine on the total production as well.The paper is a part of solution of the grant awarded by the Ministry of agriculture (NAZV) No. QF 3276 and it focuses on environmental analysis of the wine-production industry in the Czech Republic.